2022
DOI: 10.3390/ph15010089
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptor Antagonist Reduces Fibrosis and Inflammation in a Mouse Model of Alpha-Sarcoglycan Muscular Dystrophy

Abstract: Limb-girdle muscular dystrophy R3, a rare genetic disorder affecting the limb proximal muscles, is caused by mutations in the α-sarcoglycan gene (Sgca) and aggravated by an immune-mediated damage, finely modulated by the extracellular (e)ATP/purinoceptors axis. Currently, no specific drugs are available. The aim of this study was to evaluate the therapeutic effectiveness of a selective P2X7 purinoreceptor antagonist, A438079. Sgca knockout mice were treated with A438079 every two days at 3 mg/Kg for 24 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Therefore, P2X7R may influence inflammation via T cells which is indirect. The selectively P2X7 antagonist was proven to significantly inhibit the innate immune cells and upregulate the immunosuppressive-associated T cells, indicating that this antagonist may be a kind of potential treatment[ 175 ]. The effect of P2X7-blockade drug has also been demonstrated in the mouse models with advanced tuberculosis[ 176 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, P2X7R may influence inflammation via T cells which is indirect. The selectively P2X7 antagonist was proven to significantly inhibit the innate immune cells and upregulate the immunosuppressive-associated T cells, indicating that this antagonist may be a kind of potential treatment[ 175 ]. The effect of P2X7-blockade drug has also been demonstrated in the mouse models with advanced tuberculosis[ 176 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular surface of the sarcoglycan complex possesses ATPase activity; thus, when sarcoglycan-deficient muscle fibers lose their sarcolemmal integrity, they will have higher levels of extracellular ATP to trigger P2 × 7 [148]. Recent studies in Sgca −/− mice have shown that the P2X7 antagonist, A438079, reduces fibrosis and the infiltration of innate inflammatory cells into the gastrocnemius, quadriceps, and anterior tibialis muscles [149]. The immunomodulatory effect of the P2X7 antagonist makes it ideal for limiting muscle fiber damage from proinflammatory macrophages and neutrophils.…”
Section: Sarcoglycanopathymentioning
confidence: 99%
“…The P2X7 purinergic receptor (P2RX7) appears to be especially important in this respect. Genetic ablation of the P2X7 gene in mdx mice or P2RX7 antagonist administration leads to improved muscle structure and function, with reduction of inflammation and fibrosis, and increased muscle strength and endurance ( 113 , 114 ). Muscle Treg cells also support muscle repair after myocardial infarction directly via promoting cardiomyocyte proliferation ( 115 ) and indirectly via modulating M1/M2 differentiation ( 116 ).…”
Section: Subsets Of Tissue Resident Treg Cells: Characteristics and F...mentioning
confidence: 99%
“…FucT-VII (alpha-1,3-fucosyltransferase VII) is an enzyme required for PSGL-1 glycosylation to facilitate TR-Treg cell accumulation in tissues like skin and lamina propria ( 160 , 161 ). ATP released by necrotic muscle cells during muscle injury inhibits TR-Treg cell generation and functions through purinergic P2X receptors, delaying myofiber regeneration ( 113 , 114 ). In the CNS, serotonin (5-HT) produced by brain cells activates 5-HT7 receptor expressing Treg cells, supporting Treg cell expansion ( 162 ).…”
Section: Crosstalk Between Treg Cells and Tissuesmentioning
confidence: 99%